2023
DOI: 10.3389/fonc.2023.1079575
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence and survival in patients with gastrointestinal neuroendocrine tumors: A SEER database analysis, 1977-2016

Abstract: ObjectivesWe aimed to determine trends in incidence and survival in patients with gastrointestinal neuroendocrine tumors (GI-NETs) from 1977 to 2016, and then analyze the potential risk factors including sex, age, race, grade, Socioeconomic status (SES), site, and stage.MethodsData were obtained from Surveillance, Epidemiology, and End Results Program (SEER) database. Kaplan-Meier survival analysis, relative survival rates (RSRs), and Cox proportional risk regression model were used to evaluate the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Although rectal neuroendocrine tumors (RNETs) are relatively uncommon, their incidence has increased due to widespread use of screening colonoscopy and advancements in endoscopic technology [1]. The majority of RNETs are detected at stage 1 or 2, featuring excellent long-term prognosis with 5-year survival rates ranging from 74-88% [1,10,11]. Typically, 80-90% of these tumors are less than 1 cm in size, are low grade, exhibit rare metastasis (< 3%), and are diagnosed early in a well-differentiated state con ned to the submucosa [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…Although rectal neuroendocrine tumors (RNETs) are relatively uncommon, their incidence has increased due to widespread use of screening colonoscopy and advancements in endoscopic technology [1]. The majority of RNETs are detected at stage 1 or 2, featuring excellent long-term prognosis with 5-year survival rates ranging from 74-88% [1,10,11]. Typically, 80-90% of these tumors are less than 1 cm in size, are low grade, exhibit rare metastasis (< 3%), and are diagnosed early in a well-differentiated state con ned to the submucosa [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…The most common NET subtype is the gastrointestinal pancreatic NET (GEP-NET) ( 36 ). An analysis of United States cancer data showed that the incidence of gastrointestinal neuroendocrine tumors has continuously increased each decade from 1977 to 2016( 37 ). Currently, surgery is the primary therapeutic method for GEP-NETs because most GEP-NETs are inert.…”
Section: Application Of 177 Lu In Neuroendocrine T...mentioning
confidence: 99%
“…These neoplasms are mostly found in the gastrointestinal tract, pancreas, and lung [2], with the rectum being the third most frequent site of such tumors. The incidence of rectal neuroendocrine tumors has increased and was 1.3/100,000 from 2007-2016 [2][3]. Rectal neuroendocrine neoplasms (R-NENs) are classi ed into rectal neuroendocrine tumor (R-NET), rectal neuroendocrine carcinoma (R-NEC), and rectal mixed adeno-neuroendocrine carcinoma (R-MANEC) based on differentiation degree, mitotic count, and Ki-67 index.…”
Section: Introductionmentioning
confidence: 99%